Application of zinc oxide for decomposition of organic compounds - Kedruk, Y.Y.; Aitzhanov, M.B.; Gritsenko, L.V.; Abdullin, Kh.A. (Recent Contributions to Physics, 2022)
The rapid increase in population and the rapid development of industry has led to the formation of industrial effluents and pollution of water bodies with production waste harmful to their inhabitants and human health. In this regard, the task of cleaning water resources from industrial emissions, such as pesticides, organic dyes, heavy metals and other wastes, is relevant. Among transition metal oxides, zinc oxide (ZnO) is the most promising wide-gap semiconductor material, which, due to its unique properties, is actively used in various wastewater treatment methods. In this work, we studied the photocatalytic activity of nanostructured zinc oxide samples synthesized by an environmentally friendly, low-cost simple method of thermal decomposition of zinc acetate dihydrate with respect to the wide-spectrum insecticide Bi-58 New, the main active component of which is the organophosphorus compound dimethoate. Optical spectroscopy and photoluminescence were used to study an aqueous solution of Bi-58 New subjected to ultraviolet radiation in the presence of zinc oxide samples. Analytical separation was carried out by high performance liquid chromatography. An analysis of the obtained results showed the effectiveness of the application of nanostructured zinc oxide samples for the photocatalytic decomposition of insecticide Bi-58 New.
Keywords: zinc oxide; thermal decomposition; photocatalytic activity; insecticide Bi-58 New